Modelling Oilfield Scale Squeeze Treatments From Core to Reservoir - Vazquez, Oscar (SpringerBriefs in Petroleum Geoscience & Engineering, Towards Sustainable Geoenergy and Transition to Net Zero, 2023)
XII, 133 p. 53 illus., 4 illus. in color.